2010
DOI: 10.1111/j.1439-0507.2010.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of Rhodotorula infection in haematological patients

Abstract: Rhodotorula spp. are emergent opportunistic pathogens, particularly in haematological patients. However, no systematic review of this infection has been undertaken in this high-risk patient group. The aim of this study was to review all reported cases of Rhodotorula infection to determine the epidemiology and outcome of this infection in this high-risk population. The 29 reported cases were fungaemias. The most common underlying haematological disorder was the presence of acute leukaemia (65.5%). Rhodotorula m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 36 publications
5
44
3
Order By: Relevance
“…As Rhodotorula infection has low virulence in immunocompetent patients and have good prognosis and therefore require less intensive approach. [15] In this study, the duration of treatment ranged from 3 to 6 weeks for successful treatment with amphotericin B. Similarly, one study also documented similar duration of treatment (2-5 weeks).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…As Rhodotorula infection has low virulence in immunocompetent patients and have good prognosis and therefore require less intensive approach. [15] In this study, the duration of treatment ranged from 3 to 6 weeks for successful treatment with amphotericin B. Similarly, one study also documented similar duration of treatment (2-5 weeks).…”
Section: Discussionmentioning
confidence: 72%
“…[1,5,10] Similarly, other prior study also observed several risk factors (>/=3) simultaneously in one patient. [15] The incidence of CVC as risk factor is low in this study because no patient was admitted in intensive care unit. The incidence of risk factor of prolonged use of antibiotics and hospital stay is high as the isolation of Rhodotorula spp.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Rhodotorula spp. Amphotericin B † ± 5-flucytosine B-III In vitro susceptibility only to these two agents; in vitro resistance to all azoles and echinocandins 176,177 Trichosporon spp. Voriconazole C-III Preferred therapy but scarce data; in vitro resistance to fluconazole, 5-flucytosine and amphotericin B † reported 178,179 †Refers to amphotericin B deoxycholate and its lipid formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Most cases of Rhodotorula fungaemia are associated with the presence of central catheters in patients with haematological malignancies (2,8).…”
Section: Introductionmentioning
confidence: 99%